Identification of priority targets for intervention in outpatient antimicrobial stewardship - Kellie N. Arensman Hannan; Evan W. Draper; Karen A. Uecker-Bezdicek; Eric O. Gomez-Urena; Kelsey L. Jensen (Cambridge University Press, 2022)
A multimodal antimicrobial stewardship intervention was associated with a decrease in antibiotic prescribing for targeted non-coronavirus disease 2019 (COVID-19) upper respiratory infections from 27.6% in 2019 to 7.6% in 2021. We describe our approach to prioritizing departments for 3 levels of interventions in the setting of limited stewardship personnel.